Influences of hydrodynamic conditions on the biomass of benthic diatoms in a natural stream. (September 2018) - Wang, Hongwei; Li, Yong; Li, Jia; An, Ruidong; Zhang, Linglei; Chen, Min
Highlights: Benthic diatom samples were collected along transversal and lateral separately in a stream. Stream physicochemical characteristics were measured on site and tested in laboratory. 1D and 2D numerical simulation were carried out and hydrodynamic characteristics were extracted from the calculation results. The corresponding relationship between benthic diatom biomass and hydrodynamic conditions was studied both long the stream and the cross sections. Abstract: Studies on benthic algae and hydrodynamic characteristics are rarely conducted in natural streams. In this study, a natural stream was selected as a test field. First, we sampled the benthic diatoms on site. Then, we measured stream physicochemical characteristics in the laboratory. Finally, we estimated hydrodynamic characteristics using a numerical simulation. On these bases, the corresponding relations between benthic diatom biomass and stream velocity and shear stress at different sections were studied in the 1D case, and the corresponding relations between benthic diatom biomass and stream velocity and depth were studied in the 2D case. The results show that the suitable flow range for benthic diatoms is approximately 0.85–1 m/s and the suitable shear stress is approximately 24–28 N/m 2 in the 1D case. In the 2D case, the suitable velocity and stream depth are 0.9–1.1 m/s and 0.40–0.48 m, respectively. Therefore, both along the stream and in cross-section, there is always a range with suitable hydrodynamic characteristics to support a relatively high biomass of benthic diatoms. Outside of this range, however, the biomass decreases regardless of whether the values of the hydrodynamic characteristics are higher or lower. The study conclusion may provide a reference for stream ecological assessment and restoration.